Agriculture, nutrition and education: On the status and determinants of primary schooling in rural Mali before the crises of 2012 - Gelli, Aulo; Masset, Edoardo; Diallo, Amadou Sekou; Assima, Amidou; Hombrados, Jorge; Watkins, Kristie; Drake, Lesley (Elsevier, 2014)
This cross-sectional study examines the status and the determinants of primary education in food insecure areas of Mali. Net and gross enrolment ratios in primary school were between 0.3 and 0.4 for both girls and boys and well below national levels, highlighting a critical gap in terms of access to primary education. Schooling was found to respond to a broad range of determinants, including child's age and nutrition status, as well as on household consumption, on farm labour, teacher availability, and village level remoteness. Interestingly, no significant gender differences were found in terms of primary education. School meals were found to be associated with increased enrolment, attendance and attainment. The scale of the problem in Mali strongly suggests the need for investments in education and social protection to be prioritised and funded as part of national education policy and development strategies.